Southeast Asia in the global economy a selective analytical survey - Hill, Hal (The Philippine Review of Business and Economics, 2017)
This paper selectively surveys Southeast Asian economic development over the past half-century and anticipates some of the region's challenges if it is to progress to the ranks of developed countries. In the long sweep of development, three key features stand out. First, the region's 'initial conditions' in the early post-independence period appeared to be quite unfavorable. The literature at this time reflected the resulting pessimism. But, second, several countries belong to the very small group to have achieved historically unprecedented growth since the 1960s. The drivers of rapid growth remain contested. But the common feature has been a strong commitment to reasonably broad-based economic growth. Moreover, third, the propensity for growth in the region has spread as countries have progressively joined the regional and global mainstream. Policy regimes that favored outward orientation and prudent macroeconomic management have generally resulted in faster growth. The accurate forecasting of crises and growth decelerations has proven to be elusive, reinforcing the view that an eclectic, historical, and multi-disciplinary framework is necessary to understand the region?s long-term development dynamics.